(untitled) (Revista de Ciências Agroveterinárias, 2020)
This study set out to assess the nutritional status of peach trees in the commercial peach-growing region of Pelotas, Rio Grande do Sul. The sample includes 65 peach orchards of the Maciel, Granada, Esmeralda, and Sensação cultivars in the municipalities of Pelotas, Canguçu, and Morro Redondo during the 2018 agricultural cycle. After drying and grinding the leaf samples for an analysis of their nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), boron (B), copper (Cu), iron (Fe), manganese (Mn), and zinc (Zn) content, the results were presented in frequency distributions divided into classes based on the nutrient requirements indicated for the crop in the region, in addition to the correlations between the nutrients. Greater deficiencies were observed in nitrogen, copper, iron, and zinc content. However, potassium content was found in the “above normal” class for most of the samples, and there were correlations between P/Ca, P/Cu, Ca/P, Ca/Mg, and Ca/B. An insufficient use of the tools to assess the nutritional status of the orchards was observed, especially the leaf diagnosis, which led to the inappropriate use of fertilizers and the consequent nutrient imbalance in the plants.